Cyanogenesis of wild lima bean (Phaseolus lunatus L.) is an efficient direct defence in nature. - Daniel J Ballhorn; Stefanie Kautz; Martin Heil; Adrian D Hegeman (PLoS ONE, 2009)
In natural systems plants face a plethora of antagonists and thus have evolved multiple defence strategies. Lima bean (Phaseolus lunatus L.) is a model plant for studies of inducible indirect anti-herbivore defences including the production of volatile organic compounds (VOCs) and extrafloral nectar (EFN). In contrast, studies on direct chemical defence mechanisms as crucial components of lima beans' defence syndrome under natural conditions are nonexistent. In this study, we focus on the cyanogenic potential (HCNp; concentration of cyanogenic glycosides) as a crucial parameter determining lima beans' cyanogenesis, i.e. the release of toxic hydrogen cyanide from preformed precursors. Quantitative variability of cyanogenesis in a natural population of wild lima bean in Mexico was significantly correlated with missing leaf area. Since existing correlations do not by necessity mean causal associations, the function of cyanogenesis as efficient plant defence was subsequently analysed in feeding trials. We used natural chrysomelid herbivores and clonal lima beans with known cyanogenic features produced from field-grown mother plants. We show that in addition to extensively investigated indirect defences, cyanogenesis has to be considered as an important direct defensive trait affecting lima beans' overall defence in nature. Our results indicate the general importance of analysing 'multiple defence syndromes' rather than single defence mechanisms in future functional analyses of plant defences.